Diseño de un prototipo scada inalámbrico, implementando el protocolo de comunicación ZigBee. - Granda Bautista, Carlos Alberto. (2016)
The present thesis called "Design of a wireless SCADA prototype, applying the ZigBee communication protocol" lies within the area of automatic control and more specifically in the acquisition of data and wireless communication. Its main objective was to implement a wireless SCADA system supported by the programming platform LabVIEW and the ZigBee communication protocol. The design of such a system consisted of the development of an interface that allowed the emulation of the tank filling process and in turn enabled a flexible and completely remotely controllable acquisition, analysis and visualization by the user. The subsequent results obtained from the simulations of the process and the signal range testing were then presented. An Arduino card was used for data acquisition, which facilitates the interaction with the LabVIEW software through its interface called LIFA. Additionally, to establish wireless communication, XBee modules were employed, the very same which are used by the ZigBee communication protocol, plus its programming software is completely free. Finally, once finished with the design and implementation of the SCADA system, the conclusions reached, mainly oriented to the fulfilment of the main objectives, and the respective recommendations in regards to the operation of the system were presented.